1083 Nightmares Are Negatively Associated With Immediate Memory And Visuospatial Performance In Individuals With Ptsd. (27th May 2020) - Bullock, A; Burns, A; Alkozei, A; Taylor, E; Grandner, M; Killgore, W
Abstract: Introduction: Disturbing dreams and nightmares are common in individuals with post-traumatic stress disorder (PTSD). At present, little research has investigated the associations between nightmares and cognition in these individuals. However, a robust body of research has shown memory and attention impairments among those with PTSD. The present study sought to investigate the potential relationships between cognitive performance and nightmares in this population. Methods: Seventy-five individuals (49 female; M age =31.8, SD age =8.8) were administered the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), the PTSD Checklist for the DSM-5 (PCL-5), the Insomnia Severity Index (ISI), the Functional Outcomes of Sleep Questionnaire (FOSQ), the Clinician-Administered PTSD Scale (CAPS), and the Disturbing Dreams and Nightmares Index (DDNSI). Five linear regressions were conducted with index scores on the RBANS subscales (immediate memory, visuospatial/constructional, language, attention, and delayed memory) as the dependent variables and PCL-5, ISI, FOSQ, CAPS symptom class subscales (intrusion, avoidance, cognition, and arousal), and DDNSI scores entered stepwise. Results: A linear regression revealed that nightmares predicted 15% of the variance in RBANS immediate memory scores ( R 2 change=.152, β =-.390, p =.003). A second linear regression revealed that nightmares predicted 9.6% of the variance in RBANS visual memory scores ( R 2 change=.096, β =-.310, p =.019). No other independent variables added to either model. None of the independent variables predicted any variance in language, attention, or delayed memory scores. Conclusion: Our analysis revealed a unique contribution of nightmares to immediate memory and visuospatial performance in individuals with PTSD. This finding was not better explained by variation in PTSD severity or sleep. Because sleep and dreams are implicated in memory consolidation, one explanation for our finding is that highly distressing trauma-related dreams (i.e. nightmares) may lack the same memory-improving qualities as ordinary dreams. Additionally, given that immediate memory and visuospatial functioning utilize working memory, perhaps nightmares and deficits in working memory share similar mechanisms. Support: W81XWH-14-1-0570